Clinical Value of Liquid Biopsy in Patients with FGFR2 Fusion-Positive Cholangiocarcinoma During Targeted Therapy - González-Medina, Alberto; Vila-Casadesús, Maria; Gomez-Rey, Marina; Fabregat-Franco, Carles; Sierra, Alexandre; Tian, Tian V; Castet, Florian; Castillo, Gloria; Matito, Judit; Martinez, Paola; Miquel, Josep M; Nuciforo, Paolo; et al. (Clinical cancer research, 2024)
FGFR2 fusions occur in 10% to 15% of patients with intrahepatic cholangiocarcinoma (iCCA), potentially benefiting from FGFR inhibitors (FGFRi). We aimed to assess the feasibility of detecting FGFR2 fusions in plasma and explore plasma biomarkers for managing FGFRi treatment. We conducted a retrospective study in 18 patients with iCCA and known FGFR2 fusions previously identified in tissue samples from prior FGFRi treatment. Both tissue and synchronous plasma samples were analyzed using a custom hybrid capture gene panel with next-generation sequencing (VHIO-iCCA panel) and validated against commercial vendor results. Longitudinal plasma analysis during FGFRi was performed. Subsequently, we explored the correlation between plasma biomarkers, liver enzymes, tumor volume, and clinical outcomes. Sixteen patients (88.9%) were positive for FGFR2 fusion events in plasma. Remarkably, the analysis of plasma suggests that lower levels of ctDNA are linked to clinical benefits from targeted therapy and result in improved progression-free survival and overall survival. Higher concentrations of cell-free DNA before FGFRi treatment were linked to worse overall survival, correlating with impaired liver function and indicating compromised cell-free DNA removal by the liver. Additionally, increased ctDNA or the emergence of resistance mutations allowed earlier detection of disease progression compared with standard radiologic imaging methods. VHIO-iCCA demonstrated accurate detection of FGFR2 fusions in plasma. The integration of information from various plasma biomarkers holds the potential to predict clinical outcomes and identify treatment failure prior to radiologic progression, offering valuable guidance for the clinical management of patients with iCCA.